A new light transmission method to evaluate the through thickness fibre alignment in transparent resin - Zal, Vahid; Yasaee, Mehdi (Elsevier, 2022)
This work presents a new method to analyse vertical alignment of short fibres inside transparent resin layers using in situ measuring of light transmission through the layer. In this method, a light source is placed on one side of the composite layer and on the opposite side, a phototransistor measures the transmitted light intensity. A feature of the alignment process causes increased light transmission with increased fibre alignment. Using this technique, alignment of short nickel coated carbon fibres inside epoxy resin layers under magnetic field were evaluated and the effect of fibre content, field strength, fibre length and resin thickness on the alignment quality were characterised. An important finding is that the ratio of fibre length and resin thickness showcases a limit to the alignment degree. Finally, an analytical model is introduced which aims to predict average fibre angles based on the sample configuration, showcasing good agreement with experimental results.
Keywords: Carbon fibres; Thin films; Fibre alignment; Light transmission